Adverse effects of antibiotics in children with cancer: are short-course antibiotics for febrile neutropenia part of the solution?. Issue 3 (4th March 2023) - Butters, Coen; Thursky, Karin; Hanna, Diane T; Cole, Theresa; Davidson, Andrew; Buttery, Jim; Haeusler, Gabrielle
ABSTRACT: Introduction: Febrile neutropenia is a common complication experienced by children with cancer or those undergoing hematopoietic stem cell transplantation. Repeated episodes of febrile neutropenia result in cumulative exposure to broad-spectrum antibiotics with potential for a range of serious adverse effects. Short-course antibiotics, even in patients with high-risk febrile neutropenia, may offer a solution. Areas covered: This review addresses the known broad effects of antibiotics, highlights developments in understanding the relationship between cancer, antibiotics, and the gut microbiome, and discusses emerging evidence regarding long-term adverse antibiotic effects. The authors consider available evidence to guide the duration of empiric antibiotics in pediatric febrile neutropenia and directions for future research. Expert opinion: Broad-spectrum antibiotics are associated with antimicrobial resistance, Clostridioides difficile infection, invasive candidiasis, significant disturbance of the gut microbiome and may seriously impact outcomes in children with cancer or undergoing allogenic hematopoietic stem cell transplant. Short-course empiric antibiotics are likely safe in most children with febrile neutropenia and present a valuable opportunity to reduce the risks of antibiotic exposure.